Case Report: 18F-FDG PET/CT Demonstrating Malignant Spread of a Pulmonary Epithelioid Hemangioendothelioma - Wu, Ruolin; Xia, Xiaotian; Hu, Fan; Zhang, Yajing; Wang, Jingjing; He, Yong; Gao, Zairong (Frontiers in Medicine, 2022)
Pulmonary epithelioid hemangioendothelioma (EHE) is a rare vascular malignancy that is typically low-to-intermediate grade. We report a 47-year-old man with a rapidly progressive pulmonary EHE who initially presented with asymptomatic pulmonary nodules. One nodule was mildly hypermetabolic on initial 18F-FDG PET/CT. Ten months later, the patient developed severe bone pain and night sweats. Repeat imaging revealed several lung lesions, diffuse pleural thickening, and multiple skeletal metastases with considerably increased tracer uptake. The patient underwent vertebral, pleural, and pulmonary biopsies and a diagnosis of advanced pulmonary EHE was made. His disease progressed despite four courses of antineoplastic therapy, after which he began palliative care. Pulmonary EHE can be aggressive and spread rapidly. Biopsy of hypermetabolic lung lesions using PET/CT guidance might enable early definitive diagnosis.